Criminal Offense of Hoarding Subsidized Fuel Oil (BBM) - Hidayat, Syarif; Cornelis, Vieta Imelda; Hamdani, Fathul; Subekti, Subekti (Lembaga Teewan Journal Solutions, 2026)
This study examines the criminal offense of hoarding subsidized fuel oil (BBM) in Indonesia. The background of the study is the recurring misuse of subsidized fuel distribution by irresponsible actors who stockpile fuel to obtain personal profit. Such practices create supply scarcity, trigger price increases, harm lower-middle-income communities, and disturb national economic stability. This research uses an empirical legal method that focuses on the identification of living law and the effectiveness of legal rules in society. The approach studies how legal norms are implemented in practice through objectively obtained facts, including public opinions, attitudes, and legal behavior. The findings show that sanctions for hoarding subsidized fuel are regulated mainly in Law Number 22 of 2001 concerning Oil and Gas, especially Articles 51 and 55, as amended by later regulations. Article 55 provides imprisonment of up to six years and a maximum fine of IDR 60,000,000,000 for misuse of the transportation and/or trading of government-subsidized fuel. Economic motives, weak distribution oversight, regulatory gaps, and price-increase momentum are key factors enabling this offense.